Checklist of vascular plant species on inselbergs in the Monumento Natural dos Pontões Capixabas, Espírito Santo State, Brazil - Arantes, Fabiula; de Paula, Luiza; Forzza, Rafaela (Biodiversity data journal, 2024)
Inselbergs are granitic and/or gneissic rocky outcrops and, in Brazil, the dome-shaped ones in the Atlantic Forest Domain are called sugarloaves ( pães de açúcar ). They have an extremely specialised vegetation with high levels of endemism. Even though, they are poorly studied and highly degraded. In north-eastern Espírito Santo State, south-eastern Brazil, the Monumento Natural dos Pontões Capixabas (MONAPC) is a federal protected area created to guard some inselbergs mainly threatened by mining, which is one of the main economic activities in the State. In this work, we provide the first checklist of the vascular plant species in this protected area. We recorded 108 species in 36 families and 75 genera that inhabit the vegetation islands on the inselbergs within the official limits of MONAPC. A new species of Pleroma (Melastomataceae) and a new species of Cololobus (Asteraceae) were discovered as new to science and they are being described in other articles.